Intravenous iron and erythropoietin therapy for postoperative anemia among orthopedic surgery patients - Huixin Chen; Jing Yu; Qing Wei; Yu Zhang; Xilin Ouyang; Shun Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Postoperative anemia is a risk factor for adverse surgical outcomes. Our study aimed to assess the role of intravenous iron and erythropoietin therapy for the rapid correction of anemia following orthopedic surgery. Methods Patients undergoing elective orthopedic surgery were prospectively enrolled and randomly divided into three groups: Control (placebo), Group 1 (IV iron monotherapy), and Group 2 [combined IV iron and recombinant human erythropoietin (rHuEPO) therapy]. Blood tests were performed preoperative (baseline) and on postoperative days (PODs) 1, 3, and 7. Results All groups demonstrated significantly lower hemoglobin (Hb) concentrations compared to baseline, with no significant inter-group differences in postoperative Hb concentrations (p > 0.05). Serum erythropoietin, ferritin, and vitamin B12 levels, and reticulocyte count increased beyond normal ranges in all groups. Significantly lower serum iron levels were observed postoperatively in all groups (p < 0.05). No significant inter-group differences in hepcidin level were observed (p > 0.05). Conclusion Postoperative treatment with combined intravenous iron and rHuEPO was ineffective in correcting postoperative anemia among orthopedic surgery patients, besides achieving higher reticulocyte counts in the first week of surgery. No improvement in mobilization of storage iron was achieved with rHuEPO. We further suggest against vitamin B12 administration during the early postoperative period.